Community Based Inundation and Flood Mitigation in Palembang City, Indonesia - Indrayani; Saputra, Rahmad Hidayat; Elvaria, Anna; Mirza, Akhmad; Najib, Ahmad; Prakoso, Agung; Anjani, Wenda Latifah (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The increasing intensity of rainfall in Palembang City has heightened the risk of hydrometeorological disasters, particularly flooding and inundation. Despite various efforts by the municipal government to mitigate these events, flooding continues to occur following episodes of high or prolonged moderate rainfall. This study analyzes flood mitigation strategies with focus on community participation in addressing recurring inundation. Data from a flood distribution map reveal 196 flood points across the city, with flood heights ranging from 20 to 50 cm, occurring on average 10-15 times annually and typically receding within 2 to 4 hours though longer durations are observed in several sub-districts. Surveys and interviews conducted in 18 sub-districts identified key contributing factors, including drainage obstruction due to waste, sedimentation, vegetation, unauthorized construction, limited catchment areas, and inadequate drainage connectivity. Additional challenges include diminished retention pond capacity caused by vegetation overgrowth, functional conversion, embankment erosion, and topographical disadvantages such as low-lying terrain. The study proposes the optimization and restoration of drainage infrastructure, community empowerment in catchment area management, and the installation of additional pumps and automated sluice gates as integrated solutions. These measures aim to enhance water flow and reduce the frequency and impact of flooding in Palembang City.